Intra- and intermolecular interactions mediated by adaptor protein Ruk/CIN85/SETA - Ilnytska, O.M.; Drel, V.R.; Shuvayeva, H.Yu.; Havrylov, S.V.; Fedyshyn, Ya.Ya.; Mayevska, O.M.; Ihumentseva, N.I.; Gout, I.T.; Buchman, V.L. (Біополімери і клітина, 2005)
Ruk/CIN85l SETA is a member of a separate and evolutionary conserved family of adapter I scaffold proteins implicated in apoptic and receptor tyrosine kinases signalling, rearrangement of actin cytoskeleton and cell adhesion, podocyte and T cell functions. Self-regulation through intra- and intercellular interactions can be supposed for RuklCIN85l SETA as this protein contains SH3 domains and proline-rich sequence, localized within one polypeptide chain, as well as C-terminal coiled-coil region. The ability of Ruk proline-rich motifs to interact with its own SH3 domains in an intramolecular fashion and coiled-coil region to mediate oligomerization between different isoforms was assessed in GST pull down experiments. It was shown that both Ruk SH3A and to a less extent SH3B domains can interact with its own proline-rich sequences in a cooperative manner, while coiled-coil region provide for isoforms oligomerization. SH3C domain appear exerts conformational constraints, imposed on coiled-coil region, restricting the level of oligomerization. We also demonstrated that the ability of exogenous ligands to interact with Ruk polyprotine motifs is changing during the course of TNFa-induced apoptosis of human myelomonocytic W37 cells.